Analisis Drug Likeness, Toksisitas GUSAR, dan Docking Senyawa Antidesma bunius sebagai Obat Hipokolesterolemik - Fatmawati, Dwi Retno; Inacahya, Yunira Setio Putri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Hypercholesterolemia is a major risk factor for cardiovascular disease and requires alternative therapies derived from natural products to minimize the side effects of synthetic drugs. This study aimed to evaluate the potential of bioactive compounds from Antidesma bunius as hypocholesterolemic drug candidates through an in silico approach, including drug likeness screening, toxicity prediction (GUSAR), and molecular docking against the HMG-CoA reductase enzyme (PDB ID: 1HWK). From 104 compounds identified via GC-MS, 52 met the Lipinski’s Rule of Five (Ro5) criteria, indicating favorable oral pharmacokinetics. Toxicity prediction using GUSAR revealed that most compounds had oral LD₅₀ values >2000 mg/kg and were classified as having low to non-toxic profiles according to OECD standards Compounds such as Farnesol, 3-Deoxy-d-mannoic lactone, and Ambrettolide were classified in toxicity class 5 to non-toxic based on their high LD₅₀ values, particularly through oral and subcutaneous routes, indicating a wide safety margin. Docking analysis showed that Ambrettolide (−6.5 kcal/mol) and Acenapthylene (−6.4 kcal/mol) had stronger binding affinities than Pravastatin (−6.2 kcal/mol), a standard control drug, suggesting that certain natural compounds from A. bunius may possess comparable or superior hypocholesterolemic activity. Furthermore, 2,4-Dihydroxy-2,5-dimethyl-3(2H)-furan-3-one displayed a promising combination of safety, pharmacokinetic properties, and binding affinity. These findings suggest that A. bunius contains several natural compounds with the potential to be developed into safe and effective herbal therapies for hypercholesterolemia.